Strategic analysis of Costco - Ostapovych, Nataliia (2025)
This thesis provides a comprehensive strategic analysis of Costco Wholesale Corporation, with the primary aim of evaluating its current market position in the North American warehouse club market, and identifying strategies for sustained growth. The central research question guiding this analysis is as follows: What strategies can Costco implement to strengthen its competitive position and ensure long-term growth in the rapidly changing retail environment? The paper will employ various strategic frameworks, including PESTEL, VRIO, Porter’s Five Forces, SWOT, SPACE, and financial analysis, to explore Costco’s internal capabilities and the external market factors that influence its future success. The recommendations, based on the SPACE analysis, will offer actionable strategies for Costco to strengthen its market position and effectively adapt to the changing retail landscape.